Kajian Hubungan Turbulensi Industri dengan Formulasi Strategi Perusahaan - Hilman Hakiem; Melda Amelia Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this paper is to discuss the study of the relationship between industrial turbulence and corporate strategy formulation, taking three articles as case studies. This paper uses a qualitative analysis approach. In analysing the influence of industrial environmental turbulence, five levels are used, level 1 to level 5: Repetitive, expanding, changing, discontinuous, and surprising. The strategy formulation is the realisation of environmental demands. It was found that turbulence in the first case study was at the fourth level (discontinuous), turbulence in the second case study was at the third level (changing), and turbulence in the third case study was at the second level (expanding). As for strategy formulation, in the first case study the company can continuously search and enter industries that have a good future and the company can succeed. In the second case study, the company can progressively improve products/services that have been successful so far to anticipate changes in customer needs. In the third case study, the company can change its products to respond to competition, or stick with the products/services that have been successful so far, reducing costs and lower prices than competitors.